2015
DOI: 10.1039/c5cp05551b
|View full text |Cite
|
Sign up to set email alerts
|

Fe– and Co–P4-embedded graphenes as electrocatalysts for the oxygen reduction reaction: theoretical insights

Abstract: Encouraged by the great promise of metal-nitrogen-carbon (M-N-C) materials in replacing Pt for catalyzing the oxygen reduction reaction (ORR), metal-P species were successfully introduced into carbon matrices in experiments and have exhibited high catalytic activity for the ORR. Here, by means of comprehensive density functional theory (DFT) computations, we investigated the origin and the mechanism of the ORR occurring on Fe- and Co-P-embedded graphenes. Our computations have revealed that the Fe- and Co-P4 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
42
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 54 publications
3
42
1
Order By: Relevance
“…For the single O atom, the most favorable adsorption site is on the Mn top site with an adsorption energy of −5.54 eV (Figure d). The adsorption energy of the single O atom is the strongest among the studied single intermediates, which indicates that the O atom has the strongest binding interaction with the MnP 2 ‐Gra surface, similar to that in previous studies (Table ) …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For the single O atom, the most favorable adsorption site is on the Mn top site with an adsorption energy of −5.54 eV (Figure d). The adsorption energy of the single O atom is the strongest among the studied single intermediates, which indicates that the O atom has the strongest binding interaction with the MnP 2 ‐Gra surface, similar to that in previous studies (Table ) …”
Section: Resultsmentioning
confidence: 99%
“…Compared with MnN 4 ‐, FeP 4 ‐, and CoP 4 ‐doped graphene, the adsorption energies on MnP 2 ‐Gra are stronger for O 2 , O, H, OH, OOH, and H 2 O, except for H in FeN 4 (Table ). In addition, edge‐site FeP 2 shows a much stronger adsorption for O 2 and H 2 O (Table ) …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[11] Furthermore, both experimentala nd theoretical results demonstrated that MÀPc an also act as promising active sites for ORR. [13] Thus, the combination of MÀNa nd MÀPi nt he prepared catalysts can afford excellent trifunctionala ctivities for ORR, HER, and OER. [12] Feng et al,b yu sing DFT,p redicted that FeÀ and CoÀP 4 moieties can activate molecular oxygen through an ideal four-electrons avenue,w hich is beneficial for ORR.…”
Section: Introductionmentioning
confidence: 96%